2007
DOI: 10.1186/1471-244x-7-64
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric assessment of suicide attempters in Japan: a pilot study at a critical emergency unit in an urban area

Abstract: Background: The incidence of suicide has increased markedly in Japan since 1998. As psychological autopsy is not generally accepted in Japan, surveys of suicide attempts, an established risk factor of suicide, are highly regarded. We have carried out this study to gain insight into the psychiatric aspects of those attempting suicide in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 30 publications
9
38
1
3
Order By: Relevance
“…Yamada et al reported that 95% and 65% of suicide attempters had mental disorders and were under psychiatric treatment, respectively [3]. In the present study, 94.3% of the subjects had mental disorders and 67.9% were under psychiatric treatment, percentages similar to those of the previous study.…”
Section: Discussionsupporting
confidence: 88%
“…Yamada et al reported that 95% and 65% of suicide attempters had mental disorders and were under psychiatric treatment, respectively [3]. In the present study, 94.3% of the subjects had mental disorders and 67.9% were under psychiatric treatment, percentages similar to those of the previous study.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are compatible with those reported by other studies (Welch 2001; Maselko and Patel 2008; Ono et al 2008; Borges et al 2010; Mandour 2012; Patel et al 2012). It has been well reported that incidence of suicide among patients with psychiatric disorders is increased by up to 5–40 times, each completed suicide case corresponds to 6–25 repeated suicide attempts (Maris 2002; Yamada et al 2007). In a prospective follow-up study by Christiansen and Jensen (2007), the risk of repetition of suicide attempts in patients with a prior history of suicide attempt was increased 37.34 %, and mortality was increased four-fold, compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of suicide attempt were extracted from the patient's record, and divided into violent and nonviolent attempts according to the operational criteria of Yamada et al [24] and subsequently analyzed. The violent suicide group was defined as follows: (1) mechanical ventilation was required for life support; (2) surgery was performed under general anesthesia; (3) the method of attempted suicide carried a high risk of death, specifically, hanging, gunshot, jumping from a high place, inhalation of gas, solvents, or other agricultural chemicals, thermal injury, or drowning.…”
Section: Methodsmentioning
confidence: 99%